Effect of Natural Antioxidants on the Stability of Linseed Oil and Fish Stored under Anaerobic Conditions - Kinga Śpitalniak-Bajerska; Antoni Szumny; Alicja Zofia Kucharska; Robert Kupczyński (Journal of Chemistry)
Vegetable and animal oils are susceptible to the oxidation of their lipid components on storage. Polyphenols from apple peels are investigated as potential natural antioxidants used for stabilizing polyunsaturated fatty acid and preventing oxidation. The aim of this study was assessing the antioxidant efficacy of apple pomace as natural antioxidant in linseed and fish oils, stored in anaerobic conditions. Apple pomace was added to the linseed and fish oils stored for eight weeks to evaluate the antioxidant activity of their polyphenolic components. The total phenolic content, activity of DPPH, ABTS•+, FRAP, acid value (AV), peroxide value (PV), and fatty acid profile were analyzed in storage tests. We found that apple pomace, regardless of the oil content of the formulation, was capable of blanking 2,2-diphenyl-1-picrylhydrazyl radicals. The highest ability to reduce Fe3+ ions occurred in the samples containing 30% of the fish oil. The use of apple pomace comprising polyphenolic compounds improves the stability of linseed and fish oils in storage tests. Polyphenols in apple pomace show a high antioxidant potential, as indicated by their values of DPPH, ABST•+, and FRAP. The addition of apple pomace resulted in limiting the acid and peroxide values of the samples during storage.